Does Almsgiving Make Us Happier? A Study of Almsgiving (Shodaqoh-Philanthropy) and Self-Awareness on Individual Happiness - Ramadhani, Yasmin Salsabila; Hidayati, Isnaya Arina Hidayati (Asian Journal of Islamic Psychology, 2025)
Everyone desires happiness. Happiness can be achieved through many things, one of which is carrying out positive activities, namely almsgiving (philanthropy). Almsgiving itself must be done with complete self-awareness. Awareness that almsgiving comes from self-motivation to do something good. Therefore, self-awareness is an essential aspect of giving alms. This research aims to determine the relationship between alms (philanthropy) and self-awareness of happiness. This research method is a correlational quantitative method that uses the Alms Scale (philanthropy), Self-Awareness Scale, and Happiness Scale measuring instruments. The sample consisted of 155 people, with the criteria being active students at the Faculty of Psychology, ***, class 2019-2022. The sampling technique used is incidental sampling. The data analysis used was a multiple linear regression analysis using SPSS 23 for Windows. The results of the major hypothesis in this research show that there is a significant relationship between happiness and the alms (philanthropy) variable and the self-awareness variable sig 0.018 (P Value < 0.05), with an effective contribution of 7.5%. The results of the minor hypothesis show that there is a significant positive relationship between alms (philanthropy) and happiness with a correlation coefficient value of rxy = 0.213 with a minor hypothesis of 0.030 (Sig 2-tailed < 0.05) and an effective contribution of 4.2%. The minor hypothesis on the self-awareness variable shows that there is no significant positive relationship with the happiness variable of rxy=0.190 with a minor hypothesis of 0.053 (Sig 2-tailed <0.05) and an effective contribution of 3.3%. This research provides implications for individuals on how to achieve happiness through spiritual experiences from charity activities, especially for people in need.